CORRELATION DEGREE SERPENTINIZATION OF SOURCE ROCK TO LATERITE NICKEL VALUE THE SAPROLITE ZONE IN PB 5, KONAWE REGENCY, SOUTHEAST SULAWESI - Bahtiar, Wisnu Indra; Patonah, Aton; Rosana, Mega Fatimah (Journal of Geological Sciences and Applied Geology, 2022)
The PB5 study area, Konawe district, Southeast Sulawesi is a mining area included in the IUP of PT Sulawesi Cahaya Mineral which is dominated by serpentinized ultramafic rocks. Geological mapping, drilling data, petrographic analysis, X-Ray Fluorescence (XRF), and magnetic susceptibility are used to identify the characteristics of serpentine minerals, characteristics of serpentinization levels, and the correlation of serpentinization levels to nickel laterite levels in the study area. The serpentine mineral types in the study area are lizardite, chrysotile, and antigorite resulting from the alteration of olivine and pyroxene minerals. Lizardite is characterized by mesh, bastite, and hourglass textures. Chrysotile is characterized by filamentous textures and antigorite is characterized by interpenetrating and interlocking textures. The serpentined rocks are predominantly low serpentine with the mesh and bastite textures of the lizardite characterizing the early mineral alteration processes of olivine and pyroxene. Antigorite begins to be present in rocks that experience medium-high serpentinization levels and indicates that antigorite is the result of a high-intensity serpentinization process.  The serpentinization level of the study area is divided into 3 (three) types, namely (1) low serpentinization characterized by the serpentine distribution of 0%-39%, LOI <7%, and magnetic value of 0o-5o, (2) medium serpentinization with the serpentine distribution of 40%-59%, LOI 7-10%, and magnetism value of 5o-10o, and (3) high serpentinization characterized by the distribution of 60%-100%, LOI >10%, and magnetism value >10o. Rocks that experience low serpentinization and medium serpentinization levels have a fairly good nickel content development with Ni concentration factors of 5.13 units and 4.34 units. While rocks that experience a high level of serpentinization have poor nickel development with a Ni concentration factor of 2.43 ppm.